Middle Fossa Encephaloceles Treated via the Transmastoid Approach: A Case Series and Review of the Literature. Issue 5 (12th August 2021) - Scullen, Tyler; Freeman, Zane; Mathkour, Mansour; Lockwood, Joseph; Aslam, Rizwan; Jackson, Neal; Amenta, Peter S
Abstract: BACKGROUND: Middle fossa (MF) encephaloceles are rare lesions resulting from herniation through defects in the tegmen tympani or mastoideum. Underlying etiologies and clinical presentations are variable. Surgical goals include fistula obliteration, resection of nonfunctioning parenchyma, and dehiscence repair. The middle cranial fossa approach (MCFA), transmastoid approach (TMA), and combined (MCFA + TMA) approaches have been described. The minimally invasive TMA provides excellent exposure of the pathology and allows for ample working room to repair the defect. OBJECTIVE: To present short-term follow-up results in patients treated via the TM repair at our institution. METHODS: A retrospective review of patients with symptomatic encephaloceles treated via the TMA by our multidisciplinary team. Patient demographics, clinical presentations, intraoperative findings, repair technique, and outcomes were highlighted. RESULTS: A total of 16 encephaloceles in 13 patients were treated. Defect etiologies included spontaneous (50.0%), secondary to chronic infection (25.0%), or cholesteatoma (18.8%). Defects were most often within the tegmen mastoideum (68.8%). Average length of surgery was 3.3 h (95% CI: 2.86-3.67) and length of stay 3.9 d (95% CI: 3.09-4.79). On short-term follow-up (average 11.5 mo), no patients experienced postoperative cerebrospinal fluid leak or recurrence. The majority of patients (83.3%) experienced confirmed improvement or stabilization of hearing. CONCLUSION: MF encephaloceles present with various clinical manifestations and result from multiple underlying etiologies. The TMA is an alternative to craniotomy and our short-term results suggest that this approach may be utilized effectively in appropriately selected cases.